Elevated Triglyceride Level Is Independently Associated With Increased All-Cause Mortality in Patients With Established Coronary Heart Disease: Twenty-Two–Year Follow-Up of the Bezafibrate Infarction Prevention Study and Registry. (March 2016) - Klempfner, Robert; Erez, Aharon; Sagit, Ben-Zekry; Goldenberg, Ilan; Fisman, Enrique; Kopel, Eran; Shlomo, Nir; Israel, Ariel; Tenenbaum, Alexander
Abstract : Background—: The independent association between elevated triglycerides and all-cause mortality among patients with established coronary heart disease is controversial. The aim of this study was to investigate this association in a large cohort of patients with proven coronary heart disease. Methods and Results—: The study cohort comprised 15 355 patients who were screened for the Bezafibrate Infarction Prevention (BIP) trial. Twenty-two–year mortality data were obtained from the national registry. Patients were divided into 5 groups according to strata of fasting serum triglycerides: (1) low-normal triglycerides (<100 mg/dL); (2) high-normal triglycerides (100–149 mg/dL); (3) borderline hypertriglyceridemia triglycerides (150–199 mg/dL); (4) moderate hypertriglyceridemia triglycerides (200–499 mg/dL); (5) severe hypertriglyceridemia triglycerides (≥500 mg/dL). Age- and sex-adjusted survival was 41% in the low-normal triglycerides group than 37%, 36%, 35%, and 25% in groups with progressively higher triglycerides ( P <0.001). In an adjusted Cox-regression for various covariates including high-density lipoprotein cholesterol, each 1 unit of natural logarithm (Ln) triglycerides elevation was associated with a corresponding 6% ( P =0.016) increased risk of 22-year all-cause mortality. The 22-year mortality risk for patients with severe hypertriglyceridemia was increased by 68% when compared with patients with low-normal triglycerides ( P <0.001). Conclusions—: In patients with established coronary heart disease, higher triglycerides levels are independently associated with increased 22-year mortality. Even in patients with triglycerides of 100 to 149 mg/dL, the elevated risk for death could be detected than in patients with lower triglycerides levels, whereas severe hypertriglyceridemia denotes a population with particularly increased mortality risk. Abstract : Supplemental Digital Content is available in the text.